Differentiate the following, y=(2x-4)^3

dy/dx = 3(2x-4)^2 x 2
dy/dx= 6(2x-4)^2
dy/dx =24(x-2)^2

Answered by Charlie G. Maths tutor

5034 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What are the main factors when deciding whether or not the Poisson distribution is a suitable model?


Find the derivative of f(x)=x^3 sin(x)


f(x) = (4x + 1)/(x - 2) with x > 2. Find a value for 'x' such that f'(x) (first derivative of f(x) with respect to x) is equal to -1.


Find the first derivative of f(x) = tan(x).


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences